Analisis Efisiensi Lembaga Amil Zakat terhadap Pengentasan Kemiskinan - Royyan Ramdhani Djayusman; Muhammada Khafid Abdillah (University of Darussalam Gontor, 2015)
Collection and Distribution of Zakah Funds to Mustahiq is the main goal of Amil Zakah Institution (LAZ). In Its Management, Laz Ummat Sejahtera has program to reach its target. Zakah funds, both collection and distribution funds must be efficient, because LAZ USP is a trusthworthyand professional institution of Zakah that belongs to society. This research aims to analyze the efficiency rate of zakah funds on LAZ USP in poverty allevation and to measure the influence of staff management to the efficiency of zakah funds. The researcher use interviewand documentation method. The interview was held to the staff LAZ USP. This research is a field research in form of quantitative by processing data which is obtained from documentation of financial reports LAZ USP 2008-2013. The standard to measure the efficiency is Data Envelopment Analysis (DEA). DEA is a nonparametric method. It is a linear programming model, used to measure technical efficiency. The analysis will show scale 0 to 1 or 0% to 100% on the zakah funds, according to its efficiency rates. In spite of that, this research will use multiple regression to know the influence of staff managements to efficiency of Zakah Funds. The Analysis presented the efficiency rate in 2008-2009 is still in inefficiency condition, because the efficiency rate in 2008 is 97,8% and in 2009 is 99,7%. In 2010 to 2013, the efficiency rate is 100%. It indicates the maximumwas reached. The analysis with multiple regression shows that the whole management of staff has a significant influence to the efficiency of Zakah Funds. But, personally, only program management that has a significant influence to the efficiency of Zakah Funds with T Count is 2,161 and T Table is 2,02, and = 0,05.Finally, Researher hopes to LAZ USP to keep its efficiency of Zakah Funds, because collection and distributionof Zakah Funds is the main Goal of LAZ. It can be done by improving the management of staff LAZ USP, especially program management.